2022
DOI: 10.1097/iae.0000000000003557
|View full text |Cite
|
Sign up to set email alerts
|

Validation of an Automated Fluid Algorithm on Real-World Data of Neovascular Age-Related Macular Degeneration Over Five Years

Abstract: Background/Purpose: To apply an automated deep learning automated fluid algorithm on data from real-world management of patients with neovascular age-related macular degeneration for quantification of intraretinal/subretinal fluid volumes in optical coherence tomography images.Methods: Data from the Vienna Imaging Biomarker Eye Study (VIBES, 2007(VIBES, -2018 were analyzed. Databases were filtered for treatment-naive neovascular age-related macular degeneration with a baseline optical coherence tomography and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…OCT imaging has become the gold standard for the diagnosis and grading of DME. Current evidence shows that different OCT biomarkers (IRF, SRF, ELM/EZ integrity, and HRF) are particularly related to DME outcomes, even more than the central retinal thickness [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 25 , 26 , 32 , 33 ]. Although these OCT biomarkers have been correlated with both pre-treatment and post-treatment anatomic and functional outcomes (e.g., retinal thickness and visual acuity), they have different pathogenetic characteristics and, therefore, represent different aspects (phenotypes) of DME.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…OCT imaging has become the gold standard for the diagnosis and grading of DME. Current evidence shows that different OCT biomarkers (IRF, SRF, ELM/EZ integrity, and HRF) are particularly related to DME outcomes, even more than the central retinal thickness [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 25 , 26 , 32 , 33 ]. Although these OCT biomarkers have been correlated with both pre-treatment and post-treatment anatomic and functional outcomes (e.g., retinal thickness and visual acuity), they have different pathogenetic characteristics and, therefore, represent different aspects (phenotypes) of DME.…”
Section: Discussionmentioning
confidence: 99%
“…AI previous algorithms have been considered to follow changes of IRF and SRF volumes over time, which may aid clinicians to assess disease activity and treatment response [ 25 , 26 , 33 ]. Although it is incredibly difficult to make comparisons between different algorithms used in the different studies, our results about an AI quantification approach have shown excellent accuracy and reproducibility of this AI algorithm in DME.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While CST is still used as an anatomical outcome measure in clinical trials, it is neither a reliable indicator of disease activity nor does it show a meaningful correlation with visual function over time. [29][30][31][32][33] Pawloff et al applied a precision AI uid algorithm to more than 2400 eyes to assess the correlation of (three-dimensional) retinal uid volumes and (twodimensional) central retinal sub eld thickness, demonstrating a surprisingly low correlation of r=0.57 in nAMD. [32] With the increasingly important role of retinal imaging in clinical trials, there has been a growing trend towards centralizing decisions on patient eligibility and disease monitoring in RCs.…”
Section: Discussionmentioning
confidence: 99%
“…There was good agreement for both the segmentation and detection of lesions between clinicians and the network (dice scores ≥ 0.75 for all features). Two applications with validated automated DL segmentation algorithms are currently commercially available: RetinAI (Medical AG, Switzerland) and RetInSight (Vienna, Austria) [ 137 ].…”
Section: Selected Retinal Diseases For Which Ai-based Tools Have Been...mentioning
confidence: 99%